Age-Related Changes in the Canine Aorta. Issue 2 (March 2021) - Yang, Ching; Kohnken, Rebecca
Degenerative changes in the aorta are commonly observed in both dogs and humans, and those changes that occur with age morphologically overlap with those observed in genetic or degenerative diseases. Therefore, recognition of age-related aortic changes is important for diagnosticians, as such histologic findings should be distinguished from lesions of specific diseases. The aortas from 37 dogs without clinical cardiovascular disease ranging in age from 2 months to 15 years were divided into 3 cohorts to assess age-relatedness, and evaluated histologically using standardized nomenclature and diagnostic criteria adapted and modified from the human literature. We found that the histopathologic severity scores for intimal thickening, translamellar medial fibrosis, loss of smooth muscle cell nuclei, and medial microcalcification were higher in older dogs, whereas the scores for both intralamellar and translamellar mucoid extracellular matrix accumulation ("cystic medial necrosis") were not different among age groups. Dogs with translamellar medial fibrosis and aortic medial microcalcification were significantly older compared with dogs without these findings, while the presence of aortic medial chondro-osseous metaplasia was not related to age. Taken together, we demonstrate a range of age-related aortic histologic changes in dogs without clinical cardiovascular disease and suggest that integration of signalment and clinical data can aid in the differentiation of such findings from non-age-related disease processes.